Suten Games: Exploration of Empirical and Theoretical Probability for Junior High School Mathematics Learning - Oktaviani, Dewi; Kinasih, Dewi (Ethnomathematics Journal, 2023)
Suten is one of the local games often played for determining a purpose fairly. The game is played in pairs by choosing Elephant, Ant, or Man by each player. The choosing is one of the applications of the probability concept learned by students of the junior-high school. The use of the game in the instructional process can aid students in relating the probability concept they learn to real events. The objective of the present study is to explore the concepts of empirical and theoretical probabilities in the Suten game. The study is descriptive qualitative with an ethnographic approach to present detailed description and analysis concerning the Suten game in relation to probability material. Research results show the finding of the concepts of empirical and theoretical probabilities in the Suten game, especially in showing whether or not that Suten is a fair game. The game can be used in mathematics learning to introduce to students the concepts empirical probability, sample space, sample point, and theoretical probability. In addition, positive aspects can be obtained when the Suten game is integrated in learning such as, among others, inter-appraisal of decisions, training intuition, and using the abilities of creative thinking in searchimg for strategies.